Problem and algorithms of structural identification of multivariable stabilization plant with an arbitrary dynamics (by the example of the helicopter with cargo bracket) - Blokhin, Leonid; Krivonosenko, Alexandr; Vovk, Vladimir; Bezkorovayniy, Yuri (My University, 2009)
Features of statements and maintenances of the researches, that stages providing creation of new competitive or modernized systems of "stiff" stochastic stabilization of mobile objects in space and orientation with extremely achievable frontiers quality are discussed. A new problem and algorithms of structural identification of required models of dynamics of multivariate object of stabilization with an arbitrariness in dynamics are under stochastic controllable and uncontrollable influences as a base stage of planned works, are considered more detail. Особливості заяви і змісту досліджень, що етапи передбачають створення нових конкурентоспроможних або модернізованої системи "жорсткої" стохастичною стабілізації рухливих об'єктів у просторі і орієнтацію з надзвичайно досяжне якість кордонів обговорюються. Нова проблема і алгоритмів структурної ідентифікації необхідних моделей динаміки багатовимірних об'єктів стабілізації з свавіллям в динаміці перебувають під стохастичною контрольованих і неконтрольованих факторів, як база етап запланованих робіт, розглядаються більш докладно.
Keywords: structural identification; 3D modeling; структурна ідентифікація; 3D моделювання